WEB-BASED LOGISTIC DEMAND INFORMATION SYSTEM DESIGN AT RAHARJA UNIVERSITY - Khasanah, Dewi Nur; Wulandari, Siti; Dwi, Rosmawati (ADI Journal on Recent Innovation (AJRI), 2019)
In the present Information Technology (IT) is highly developed. Even in daily life, everything is computerized, such as in companies, schools, offices, shopping centers, and many more. Nearly the average has used a computerized system for service and information presentation. With this computerized system, it is expected to be able to facilitate in all aspects of life. The purpose of this study is to design a logistics goods demand system at Raharja College. The approach taken in this report is by direct observation through field studies. To examine how the procedure for processing logistical demand data at Raharja University. Data processing is very important to produce a logistical demand report. The logistical demand data processing system that runs currently is semi computerized using Microsoft office Excel. So that errors often occur in the calculation of logistics goods demand reports and the processing process becomes less effective in terms of time. This study uses a SWOT analysis method, system requirements elicitation, and system modeling using UML (Unified Modeling Language) to visualize, which is then implemented with the Hypertext Preprocessor (PHP) programming language with the MySQL-Server database as the database used. With the logistics demand system, it can make it easier for the finance department to produce accurate logistics goods demand reports with fast time, so that it can create effective and efficient performance, and can support evaluation in internal control for the leadership of the report.